THE IMPACTS OF IMPLEMENTING MERDEKA BELAJAR CURRICULUM ON THE QUALITY OF SENIOR HIGH SCHOOL EDUCATION IN INDONESIA: A SCOPING REVIEW - Albertus Erico Jerry Krisna Nugroho; Sugiyanto Sugiyanto; Singgih Prihadi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Education in Indonesia faces serious challenges after the COVID-19 pandemic, marked by a decline in academic achievement, including PISA scores in reading literacy, mathematics, and science. To address these issues, the Ministry of Education, Culture, Research, and Technology launched the Merdeka Curriculum as an effort to increase learning flexibility, foster creativity, and strengthen 21st-century competencies. However, the implementation of this curriculum still faces obstacles, particularly regarding teacher readiness, resource limitations, and variations in school conditions. This study aims to examine the impact of the Merdeka Curriculum implementation on the quality of education at the senior high school level in Indonesia. The method used in this study is a scoping review approach with the PRISMA-ScR guidelines, which includes empirical articles published from 2020 to 2024 obtained from the Scopus, DOAJ, and ERIC databases and other specified inclusion criteria. The results of the review of 27 articles show that differentiated learning and diagnostic assessment have been proven to increase learning effectiveness; conversely, authentic and cognitive assessments still face obstacles. In addition, the development of innovative teaching modules and the implementation of project-based learning encourage students' critical, analytical, and entrepreneurial thinking skills. This curriculum also strengthens values-based education, local wisdom, and social interactions that support character building in accordance with the Pancasila Student Profile. In conclusion, the Merdeka Curriculum has significant potential to improve the quality of secondary education in Indonesia, although its success is highly dependent on teacher readiness, policy support, and equitable distribution of resources by the Indonesian government.